THE IMPORTANCE OF USING THE STEAM APPROACH IN CREATIVE THINKING - Rajabova Lobar Choriyevna (Journals Park Publishing, 2024)
STEAM education differs from other educational technologies in that it focuses on enhancing the creativity of elementary school students in an approach that includes the study of mathematics, technology, creativity, engineering and science. The integrated educational process allows us to prepare in-demand specialists in the field of engineering, design and modeling - modern professions. Innovative methods and modern technologies are the main means of using STEAM technology in the process of primary education. The article talks about the importance of the STEAM approach in the development of creative thinking in primary school students.
Keywords: primary classes, creativity, education, upbringing, thinking, self-awareness, creativity, design, mathematics, intelligence, STEAM, engineering.